AHLI WARIS TUNGGAL PEREMPUAN MENURUT HUKUM WARIS ISLAM (ANALISIS PUTUSAN AGAMA MATARAM) - Mualifah Mualifah; Ridwan Ridwan; M. Faisal (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
The purpose of this study is to determine the application of Islamic inheritance law in the settlement of inheritance disputes at the Mataram Religious Court, so that it can be seen whether there is gender discrimination in inheritance distribution according to Islamic inheritance law rules. This is done by analyzing the decisions of inheritance cases, which are decided by the Mataram Religious Court. The method used in this study is a normative legal approach which aims to analyze the decisions of religious courts related to inheritance cases. Aspects that will be studied are: Application of Islamic inheritance law in the settlement of inheritance disputes and discrimination against women in Islamic inheritance law. The results of the study show that the legal regulation of daughter inheritance in Islam is shown in Surat An-Nisa (IV): verses 11, 12, 33, 176 and in the hadiths of the Prophet. then in the Compilation of Islamic Law (KHI) the distribution of inheritance for only female children is stated in article 176, where if "a daughter if only one then she gets half the share; if two or more persons, they jointly get two-thirds of the share; and if the daughter is together with the son, then the share of the son is two to one with the daughte.